2000
DOI: 10.1207/s15374424jccp2902_2
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal Ideation in Adolescent Psychiatric Inpatients as Associated With Depression and Attachment Relationships

Abstract: Examined suicidal ideation in adolescent psychiatric inpatients as associated with depressive symptoms and attachment to mother, father, and peers. Fifty-nine adolescent psychiatric inpatients (25 male, 34 female) completed self-report measures of suicidal ideation, depressive symptoms, and attachment. Attachment to mother accounted for significant variation in levels of depressive symptoms and suicidal ideation. In addition, attachment to peers accounted for significant variation in suicidal ideation and girl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
35
1
6

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(49 citation statements)
references
References 57 publications
7
35
1
6
Order By: Relevance
“…However, unlike previous studies of suicide ideation that found positive parental attachment (DeJong, 1992;DiFilippo & Overholser, 2000) as well as parental involvement (Perkins & Hartless, 2002) to be significant predictors, our model did not.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, unlike previous studies of suicide ideation that found positive parental attachment (DeJong, 1992;DiFilippo & Overholser, 2000) as well as parental involvement (Perkins & Hartless, 2002) to be significant predictors, our model did not.…”
Section: Discussioncontrasting
confidence: 99%
“…Put another way, suicidal youths are more likely to exhibit weak attachments (DiFilippo & Overholser, 2000;Kandel, Raveis, & Davies, 1991;Perkins & Hartless, 2002). In particular, lack of parental attachment has been empirically shown to impact suicidal ideation (Adams et al, 1994) and completion (Brent et al, 1994).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Assim, os adolescentes que desenvolvem estratégias de coping defensivas e mal adaptativas, evitando o envolvimento e enfrentamento de situações geradoras de stress parecem ter desenvolvido relações de vinculação insegura (DiFilippo & Overholser, 2000). A criação de modelos internos negativos conduz uma vinculação ansiosa/insegura, revelando nos indivíduos comportamentos evitantes ou resistentes perante a preocupação sentida com a indisponibilidade e não responsivadade das fi guras de vinculação (e.g.…”
Section: Discussionunclassified
“…Nesta medida, adolescentes com uma vinculação segura parecem ser mais confi antes, pelo que o seu desenvolvimento sugere a escolha de estratégias de coping mais adaptativas (DiFilippo & Overholser, 2000). O ajustamento dos adolescentes em situações ansiogénicas e de transição, poderá assim, espelhar-se na forma como gerem as difi culdades (e.g.…”
Section: A Individuação E a Confi Guração Familiar No Desenvolvimentounclassified
“…Results indicated that lack of friendship support and perceived peer rejection were directly associated with suicidal ideation while deviant peer affiliations were related to suicidal ideation, mediated by depression and substance abuse. In fact, several other studies support the association of peer support with suicidal ideation or behavior via psychological impairment such as depression (e.g., DiFilippo & Overholser, 2000;Reifman & Windle, 1995). Whether peer functioning is directly or indirectly related to suicide, problematic peer relations remain important risk factors to be considered, especially when preventing suicidal behavior among at-risk youth.…”
Section: Microsystem-level Predictorsmentioning
confidence: 99%